Protected areas and the challenge of conserving crop wild relatives - Hunter, D.; Maxted, Nigel; Heywood, V.; Kell, S.; Borelli, Teresa (2012)
Crop wild relatives are a critical resource for sustaining future food security. It is widely recognized that many of the worlds protected areas contain CWR diversity. Despite this, it has not yet proved possible to undertake significant actions to conserve the CWR they contain. Many challenges and obstacles need to be addressed in order to improve this situation. Recent initiatives have started to address these challenges and uncovered some key lessons. still, the need for action is urgent and the paper concludes by drawing attention to the need for a global approach to conserving priority and threatened CWR in the wild.